Exploring strategies for management of in-hospital stroke in Sweden: A qualitative study. - Ilan Ben-Shabat; Kristina Lindvall; Jonatan Salzer (PLoS ONE, 2024)
Background Patients with in-hospital stroke (IHS) are discovered and treated with delays compared to community-onset stroke. This qualitative study explores current routines and clinical practices for IHS in Sweden, aiming to uncover factors influencing management and propose areas for future research and development. Methods Six physicians in charge of stroke alerts at Swedish hospitals were individually interviewed in video calls. Informants were selected from The Swedish Stroke Register, based on the hospital-specific median processing time for delivering thrombolysis or thrombectomy to IHS patients, stratified by hospital size. Transcribed interviews were analysed using reflexive thematic analysis. Results Three main themes were developed. The first emphasized the crucial step of discovering IHS and outlined possible workflow pathways, including defining the "key player" with stroke expertise and mandate to proceed with the stroke alert to immediate radiology. Subsequent themes addressed obstacles to optimal practice and suggested clear guidelines for contacting the "key player" to reduce delays, as well as offering IHS education to hospital staff. Conclusions This study identified differences in workflows for IHS management across the six included sites. A "key player" emerged as a common denominator, who was called as the initiation of the stroke alert and had mandate to proceed with the alert to immediate radiology. Clear guidelines for contacting the "key player" and increased education about IHS were suggested as possible ways to mitigate delays to activate the stroke alert.